Dominant B cell receptor clones in peripheral blood predict onset of arthritis in individuals at risk for rheumatoid arthritis. Issue 11 (8th August 2017) - Tak, Paul P; Doorenspleet, Marieke E; de Hair, Maria J H; Klarenbeek, Paul L; van Beers-Tas, Marian H; van Kampen, Antoine H C; van Schaardenburg, Dirkjan; Gerlag, Danielle M; Baas, Frank; de Vries, Niek
Abstract : Background: The onset of seropositive rheumatoid arthritis (RA) is preceded by the presence of specific autoantibodies in the absence of synovial inflammation. Only a subset of these at-risk individuals will develop clinical disease. This impedes efforts to implement early interventions that may prevent onset of clinically manifest disease. Here we analyse whether clonal changes in the B cell receptor (BCR) repertoire can reliably predict onset of signs and symptoms. Methods: In a prospective cohort study in 21 individuals at risk for RA based on the presence of autoantibodies, the BCR repertoire of paired peripheral blood and synovial tissue samples was analysed using next-generation BCR sequencing. BCR clones that were expanded beyond 0.5% of the total repertoire were labelled dominant. The relative risk (RR) for onset of arthritis was assessed using the presence of ≥5 dominant BCR clones as cut-off. Findings in peripheral blood were validated in an independent prospective cohort of 50 at-risk individuals. Based on the test cohort, individuals in the validation cohort were considered positive if peripheral blood at study entry showed ≥5 dominant BCR clones. Findings: Both in the test and validation cohort, the presence of ≥5 dominant BCR clones in peripheral blood was significantly associated with arthritis development after follow-up (validation cohort RR 6.3, 95% CI 2.7 to 15, p<1×10 −4 ). Even when adjusted for a recently described clinical prediction rule the association remained intact (RR 5.0, 95% CI 1.2 to 20, p=0.024). When individuals developed arthritis, dominant BCR clones disappeared from peripheral blood and appeared in synovial tissue, suggesting a direct role of these clones in disease pathogenesis. Interpretation: Dominant BCR clones in peripheral blood predict onset of clinical signs and symptoms of RA in at-risk individuals with high accuracy. Our data suggest that during onset of RA these clones shift from peripheral blood to the target tissue.